A Comprehensive Survey for Hiding Medical Data Based DNA Lossless Technique (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
The health information data includes reports on the patient’s condition, including addresses, names, tests, treatments, diagnoses, and medical history. It is sensitive information for patients, and all means of protection must be provided to prevent third parties from manipulation or fraudulent use. The goal of this paper presents studies of safeguard the transfer of sensitive data over an unsecured network using DNA techniques to enhance security. A comparison analysis is used to show the security issues of the various DNA-based data (ciphering, concealing, and compression) techniques that are studied and investigated. Also, in our study is to provide future researchers with the necessary knowledge to conduct data security research to develop or improve DNA-based data- ciphering, compression-hiding strategies that are more reliable, secure, and efficient. Thus, future researchers need to propose a trustworthy DNA-based data (ciphering, hiding, and compression) techniques. The result of our study appears the perceived vulnerability of medical data and health insurance to concerns of security as well as common security issues, also the nature of these common security concerns, for reducing medical data security risks.